The use of cognitive bias modification and imagery in the understanding and treatment of depression. - Browning, M; Blackwell, SE; Holmes, E (2013)
Cognitive models of depression form the natural link between neurobiological and social accounts of the illness. Interest in the role of cognition in depression has recently been stimulated by the advent of simple, computer-based "cognitive bias modification" (CBM) techniques which are able to experimentally alter cognitive habits in clinical and non-clinical populations. In this chapter, we review recent work which has used CBM techniques to address questions of aetiology and treatment in depression with a particular focus on the interface with neurobiological and social processes relevant to the illness. We find that there are early signs that CBM may be a useful tool in exploring the aetiology of depression, particularly in regard to the neural and genetic factors which influence susceptibility to the illness and response to treatment. There is also early evidence suggesting that CBM has promise in the treatment and prevention of depression. This work suggests that the beneficial effects of CBM are mediated by the interaction between cognitive functioning and environmental and social information. In summary, by providing a method for altering habitual cognitive function in experimental and clinical settings CBM techniques have begun to further the understanding of and the treatment for depression.